Enhancement of the structure, solar cells and vibrational studies of undoped CuCr2O4 and La-doped CuCr2O4 semiconductor compounds. Issue 4 (April 2022) - Rajeswari, G.; Prabavathi, N.; Tamizhdurai, P.; Prakasam, A.; Kumar, G.
Abstract: In the present paper, we report the successful synthesis of spinel-type of CuCr2 O4 and La doped CuCr2 O4 semiconductor nanoparticles by a microwave method. Starting with the precursor complex, this technique includes the creation of homogenous solid intermediates, which reduces atomic diffusion pathways during the microwave process. CuCr2 O4 and La doped CuCr2 O4 were characterized by the following analytical methods for instance X-ray diffraction (XRD), transmission electron microscopy (TEM), Ultraviolet–visible (UV–Vis) spectroscopy and Fourier transform infrared spectroscopy (FTIR). The results demonstrated that modifying the precursor had a significant impact on the size, solar cell size, as well as reaction period of synthesizing CuCr2 O4 and La doped CuCr2 O4 . The impacts of precursors on the morphological and structural characteristics of CuCr2 O4 and La doped CuCr2 O4 were examined for the first time in this publication. Abstract : Chemical synthesis, Nanostructured materials, CuCr2 O4, Lanthanum, Inorganic materials.